Media effect of Korean pop culture toward the gender identity of Malaysian university male - Au, Xin Yi; Nam, Siaw Yuan; Soo, Jun Kit; Tan, Shu Yee; Wong, Pui Eng (2022)
The expansion of Korean culture had a significant impact in many areas, including culture, lifestyles, and arts. The influence of Korean culture has been widely discussed in different fields. However, the impact of Korean culture on gender identity is limited. The study aims to fulfill three primary objectives: firstly, (a) To explore the understanding of hegemonic and soft masculinity. (b) To discover the effect of media on gender identity. (c) To find out the extent of the acceptance of soft masculinity in the media. This qualitative study utilized in-depth interviews with 10 UTAR students aged between 21 and 23. The thematic analysis approach was used to analyze the data. Among the 10 students, all of them had a positive attitude toward Korean popular culture, and they agreed that the mass media heavily reconstructed their gender identity in terms of their physical appearance and internal characteristics. This research study helped understand the media effect of Korean pop culture on the gender identity of Malaysian males.